Restaurant App - قادري, رزان (My University, 2021)
The Triple Restaurants Application: It is three applications is used to serve customers and restaurant owners ,to make their work easier, to increase the number of restaurant customers and to increase restaurant profits ,because there is a specific application for customers to view the menu, order meals, track the order, view offers and get notifications about The latest developments and other offers , the manager application, which is an application only for the restaurant manager that allows him to control prices, offers, pictures and others on the GUI of the customer application, the delivery man application: an application that helps the delivery man to know new orders, their locations and the orders that have been delivered and Locations of requests from Google Maps to make his work easier and access to them on time.